Dynamic Economic Dispatch Problems: PSO Approach - Mohd Ruddin Ab Ghani; Saif Tahseen Hussein; Nur Huda Mohd Amin; Zanariah Jano; Tole Sutikno (Universitas Ahmad Dahlan, 2017)
Due to limited availability of coal and gases, optimization plays an important factor in thermal generation problems. The economic dispatch problems are dynamic in nature as demand varies with time. These problems are complex since they are large dimensional, involving hundreds of variables, and have a number of constraints such as spinning reserve and group constraints. Particle Swarm Optimization (PSO) method is used to solve these challenging optimization problems. Three test cases are studied where PSO technique is successfully applied.